STUDI KUALITATIF TENTANG BUDAYA DISIPLIN DALAM MENINGKAT ETIKA BELAJAR SISWA - Nugroho, Haryo; Subiyanto, Subiyanto; Rasidi, Rasidi (Universitas Muhammadiyah Magelang, 2015)
This research aimed to know the culture of student?s discipline and ethics at the Muhammadiyah 1 Alternatif elementaryschool in Magelang.Research design use qualitative descriptive research to interpret an existing data and describing by sentence that finally we can conclude. The analysis of the data derived from observation, interviews, documentation, then the data is grouped later reunited subsequent theories have to be justified by the research and finally drawn a condusion that can understood. The object of this study include the culture of discipline and ethics of student learning. Culture of discipline and learning ethics were collected by triangulation method. The study subjects consisted of principals, teachers, and students at Muhammadiyah 1 Alternatif Elementary School Magelang City. The student?s discipline and learning ethic can be observe from 14 indicator and 33 item were measure using interviews and observation instrument. Data analysis technique used descriptive qualitative analysis and thematic analysis.The result show that culture has an influence student discipline in supporting student learning ethics. A good student discipline will be a good student learning ethics.